The north-western grasslands of Tunisia; a feed resource to efficiently produce a healthy sheep meat - Hajji H; Mekki I.; Smeti S.; Atti N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In the North West region of Tunisia, lambs are produced indoors (S) or at pasture (P).The main meat breeds are: Barbarine (BB), Noire de Tibhar (NT) and Queue Fine de l’Ouest (QFO). This study investigated the effects of feeding system (S vs. P) and breed (BB, NT, QFO) on lambs’ growth and carcass and meat quality. 36 male lambs (20 kg body weight) were used. S lambs received an increasing amount of concentrate (300 to 600g) with 500g of oat hay. P lambs ingested the same amount of hay and grazed for 6 hours in natural grassland for which the botanical composition was determined. After 67days, the lambs were slaughtered, carcasses were dissected and meat quality was studied. The pasture was composed of 45% grasses, 14% legumes and 41% other species. The average daily gain (ADG) was lower for P than for S lambs (94 vs. 111 g/day). The NT breed had the highest ADG (125 g/day). P lambs accumulated more muscle and less fat than S lambs, with no difference between breeds. In contrast, although the meat of both feeding systems had the same macrochemical composition, saturated fatty acids and lipid oxidation index of meat were higher in S than in P meat.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)